Smart Homes and Blockchains: A Smart Door Lock Operated by a Smart Contract - Riccardo Sottini; Vitor Jesus (Cloud Computing and Data Science, 2025)
The integration of blockchain technology into numerous domains has demonstrated its ability to address transparency, security, and cost-effectiveness. Furthermore, with its association with cryptocurrencies, it allows seamless integration with payment systems. We report on a project that investigates the practical elements of using blockchains and smart contracts in Cyber-Physical Systems (CPS) in multi-party scenarios involving the delegation of (digital) keys being handed over temporarily. Specifically, we implemented a smart lock system for a conventional front door whose digital “keys” were stored and managed (e.g., digitally handed over) via smart contracts over a public blockchain (Polygon, specifically). Through our evaluation, we found that modifying permissions takes around 5 seconds, primarily due to the time required to update the blockchain, whereas checking for access is instantaneous.